An analysis of the effectiveness of the strategies used to enhance service delivery in the public sector: a case of the Registrar General Department - Denhere, Simbarashe (Midlands State University, 2015)
This research study was a case of the Registrar General Department and it sought to evaluate the effectiveness of the strategies used to enhance service delivery in the public sector. The research objectives were ,to identify the key strategies adopted by The Registrar General’s department, in improving service delivery, to establish the ideal benchmark requirements for the strategies used that is the use of information and communication technology (ICT) and performance management to be effective in enhancing service delivery, to establish areas of concern not addressed by the existing strategies and the reasons why and to come up with recommendations designed for feasible improvements in making full utilization of the strategies adopted. The study was carried out under the assumption that the sampling method will represent the entire total population of respondents and the methodology to be used to enable accurate data collection. Descriptive research design was chosen to describe chosen because the population was wide and varied across the employees at the Registrar General Department as well as the citizens who had been served and those seeking services. Selltiz et al (1989) points out that the descriptive survey method can be used to collect information from the whole cross section of the population. Primary data was collected using questionnaires. The population for this research consist of managers, processing officers at the registrar general department and citizens of Zimbabwe who are approximately 12600 billion. For sample size, the researcher came up with a total of (68) respondents which comprised of (35) customers (3) supervisors and (30) employees. Stratified random sampling and purposive sampling techniques were used for data collection and the data was presented using tables as these made it easier to express, summarize and present the findings The findings indicated that vast efforts were being done by The Registrar General department in implementing Results Based Management system and that was the main variable which they want to adopt in order to improve on their services. The researcher then concluded that service delivery at the Registrar General has improved from the past years but is still not satisfactory and effective to the customers and the reason for this being the variables which enhance service delivery are not well implemented. The service delivery implementation of the Registrar department is concentrating much on implementing the ZimAsset and they are based on using the Results Based Management system and it is their priority. In house Training and development is being done at the Registrar General Department although mostly technical skills being covered than those of customer care. Customers indicated that the employees are rude and not helpful. Some customers accuse the employees to be corrupt and not transparent in the way they do their job. The Results Based Management is being used as the performance management system. Most employees to date now understand the system and are now working in conjunction with the Zim Asset strategies. The use of compensation and benefits to improve service delivery is being done except that the government is in debt and because of the current economy that Zimbabwe is in it is difficult to use financial incentives thus the Registrar General department has to focus on other methods that are crucial.